N14 The satisfaction of IBD patients' nursing care in biological therapy. Observational study. (30th January 2023) - Napolitano, D; Cocchieri, A; Orgiana, N; Fanali, C; Poscia, A; Schiavoni, E; Bernabei, T; Amatucci, V; Turchini, L; Durini, E; Strazzeri, M; Laterza, L; et al.
Abstract: Background: Inflammatory Bowel Disease (IBD) management requires a multidisciplinary team, in which nurses have a pivotal role. Although patient care is the main focus of all clinical actions, satisfaction with healthcare professionals is an aspect of growing importance that has been related to positive clinical outcomes. In this setting, evaluating the satisfaction of the nursing provided could be a pivotal component for the satisfaction of the patient, particularly in the IBD unit, where patients in intravenous (iv) biological therapy spend a major amount of time compared to non-complicated acute hospitalization. The aim of the study is to measure the overall quality of nursing care perceived by IBD patients receiving biological therapy. Furthermore, the opinion of loyal and non-loyal patients was measured at the IBD center as a secondary objective Methods: Cross-sectional observational study to assess nursing satisfaction through the Newcastel Satisfaction Nursing Scale (NSNS). The instrument consists of two separate scales: the Scale of Nursing Care Experiences ("A") and the Scale of Nursing Satisfaction ("B"). The patient who is followed by the center, at the time of administering the questionnaire, for a period of more than 12 months, will be considered in the arm long follow-up while all patients treated at the center for a period ranging from 0 to 12 months, in those short follow-up. The study protocol was approved by the Ethics Committee. Results: Two hundred and thirty-four in biological therapy, questionnaires were administered, of these, with an excellent response rate, 200 (86.2%). The result was an overall level of satisfaction compared to the first scale "A", equal to 88.4%, while for the second scale "B" the total result was 90.7%. By analyzing the satisfaction of nursing care received, differentiating the patient between short and long follow-up, the results seem to confirm how the patient in the long follow-up positively affects satisfaction, significantly in the first scale "A" 90.5% vs 82.9% p = 0.0002 and in the second scale "B" 92.5% vs 86% p = 0.0001. The lowest average satisfaction scores were recorded in the doctor-nurse ratio and in the communicative aspects, while the highest scores are related to the empathic components and professional competence of nursing. Conclusion: In conclusion, the level of satisfaction of patients in biological therapy is high and this seems to increase significantly with time and with patient loyalty to the center (Fig. 1). Further research projects could aim to fill gaps in knowledge and validate scales of assessment of nursing skills in the field of IBD, including by structuring studies with a control cohort.